Serology for human papillomavirus - Coursaget Pierre (Instituto Nacional de Salud Pública, 2003)
Difficulties with serology for papillomavirus are associated with the large number of human papillomavirus, cross-reactions between papillomavirus, and to the diversity of lesions and target sites for infection. In addition, the expression of the papillomavirus in the superficial layers of the epithelium gives rise to the weak presentation to immunocompetent cells of viral antigens, which in turn gives rise to a weak serological response. Distinct efforts have been made in previous decades to develop more specific and sensitive serological assays. These former studies use fusion proteins and synthetic peptides, although they remain on the whole uninteresting, due to their lack of sensitivity and specificity. Only in the last few years, and principally due to the advent of various virus-like particles (VLP), have more sensitive and specific assays become available.